PEMBUDAYAAN LITERASI MEMBACA DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Vitri Astuti; Sutama; Achmad Fathoni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study focuses on the efforts to cultivate reading literacy in the Indonesian language learning at MI Muhammadiyah Karanganyar. Using a descriptive qualitative approach, this research involves the principal, second and fifth-grade teachers, and library staff as the main informants. Data were collected through observations, interviews, and documentation, then analyzed using triangulation techniques to ensure data validity. The results show that MI Muhammadiyah Karanganyar has implemented various literacy programs since 2017, including a 15-minute reading habit before lessons begin, the development of reading corners in each class, and the optimization of the school library as a literacy center. The stages of literacy cultivation are carried out through three main phases: habituation, development, and learning. Each phase involves activities that support students' reading interest, such as read-aloud sessions, book discussions, and reading reflection writing. However, this study also identifies several challenges, such as low student reading interest and limited access to engaging reading materials. To address these challenges, MI Muhammadiyah Karanganyar engages the active role of the entire school community, including teachers, the principal, and parents in supporting the literacy program. Additionally, rewarding students who are active in literacy activities is one of the strategies to enhance reading interest.